Legal Protection Analysis Of Palembang Songket Motif According To Law No. 28 Of 2014 On Copyright - Audia, Depi; Erniwati, Erniwati; Wahyuningrum, Kartika Sasi (Fakultas Hukum Dehasen, 2025)
Throughout its history, the traditional Palembang songket fabric was initially worn only by royal families and nobility. However, over time, its use has expanded to include various official events, making it a symbol of rich culture and local identity. This study aims to analyze the legal protection of Palembang songket motifs, based on the provisions set forth in Law No. 28 of 2014 on Copyright. The study also explores various factors that hinder the official registration of these motifs, despite their high cultural and economic value. The method used in this research is normative legal research, focusing on the study of laws and regulations and their implementation in practice. The findings reveal that out of 100 Pandai Sikek songket motifs, only 23 motifs have copyright certificates. Several factors hindering registration include the unknown creators of the motifs, lack of awareness regarding registration from the start, and widespread plagiarism that harms the original copyright holders. Legal protection of songket motifs is differentiated into two types: preventive protection, which includes socialization and the registration of works, and repressive protection, which involves legal enforcement against copyright violations. This research provides insights into the importance of legal protection in preserving local culture and encouraging creativity in the traditional textile industry.